(untitled) (Social Security Management Journal, 2024)
The increasing prevalence of Flexible Work Arrangements (FWAs), such as gig work, part-time work, and remote work, has raised concerns about the sustainability and adaptability of social security systems worldwide. This systematic review aims to examine the impact of these arrangements on social security programs. The problem statement emphasizes the importance of understanding the implications for social security, including changes in contributions, demographics, and the need for policy adaptation. Through a systematic approach, the review analyzes academic literature from Scopus and Econbiz databases, focusing on studies providing empirical insights into the effects of FWAs on social security systems. The findings of the review are synthesized from seven primary studies (n=7), revealing critical dimensions of the issue. Key among these is the challenges posed to social security programs, including reduced contributions due to irregular income patterns and demographic changes as the workforce ages. Additionally, the findings highlight the necessity for legal and policy adjustments to accommodate the nuances of FWAs. The review identifies several gaps in current research, particularly the need for more longitudinal studies to assess the long-term effects of FWAs on social security systems. Looking forward, this review suggests avenues for future research, emphasizing the importance of exploring the intersection of FWAs with technology and globalization. It also calls for more comprehensive studies on the efficacy of new policy adaptations in various socio-economic contexts. By offering a comprehensive understanding of how FWAs are reshaping global social security management, this review provides valuable insights for policymakers, researchers, and practitioners dealing with the dynamics of complex work and social welfare relations.